Synthesis and characterization of tetrahedrite Cu10Cd2Sb4S13 monograin material for photovoltaic application. (May 2020) - Ghisani, Fairouz; Timmo, Kristi; Altosaar, Mare; Raudoja, Jaan; Mikli, Valdek; Pilvet, Maris; Kauk-Kuusik, Marit; Grossberg, Maarja
Abstract: Cd-substituted tetrahedrite Cu10 Cd2 Sb4 S13 (TH-Cd) monograin powders were synthesized in molten CdI2 (as flux) with the aim to implement these materials as absorbers in monograin layer solar cells. Our study focuses on the influence of technological parameters, like the initial composition of precursors, the amount of CdI2 -flux and temperature of synthesis, on the elemental and phase composition and on the size and shape of powder crystals. Based on energy dispersive X-ray spectroscopy and X-ray diffraction investigations, mainly single phase tetrahedrite with a composition close to the stoichiometry of Cu10 Cd2 Sb4 S13 was formed at 480 and 495 °C. It was found that incorporation of Cd from CdI2 into formed crystals rised with increasing amount of CdI2 -flux if no other Cd source (CdS) was used. It was shown for the first time that there are peaks at 94 - 97 cm −1 and 108 - 112 cm −1 in the Raman spectra of Cu12 Sb4 S13 and Cu10 Cd2 Sb4 S13, respectively. Monograin powders grown at 495 °C were used as absorber material in monograin layer solar cells with a structure of ZnO/CdS/Cu10 Cd2 Sb4 S13 /graphite. The efficiency of the first TH-Cd monograin layer solar cell was 0.14%. The effective band gap value of Cu10 Cd2 Sb4 S13 absorber was determined as 1.3 eV.